Penghindaran Pajak: Apakah Intensitas Persediaan Memoderasi Profitabilitas dan Kepemilikan Institusional? - Najwa Aulia; Krisdiana Krisdiana (JURISMA : Jurnal Riset Bisnis & Manajemen, 2026)
This study investigates the roles of profitability and institutional ownership in explaining tax avoidance practices, while examining inventory intensity as a moderating factor among food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. A quantitative causal research design was employed using secondary data derived from published financial statements. The analytical procedure applied Moderated Regression Analysis (MRA) processed using SPSS version 29. The empirical findings reveal that higher profitability is associated with lower levels of tax avoidance, indicating a significant negative relationship. In contrast, institutional ownership demonstrates a significant positive association with tax avoidance behavior. Inventory intensity shows no direct influence on tax avoidance and does not moderate the relationship between profitability and tax avoidance. Nevertheless, the moderating test indicates that inventory intensity weakens the effect of institutional ownership on tax avoidance, suggesting its conditional role within this relationship. These findings extend empirical evidence regarding the determinants of tax avoidance and provide practical insights for corporate decision-makers, investors, and tax authorities in strengthening monitoring mechanisms and improving the understanding of corporate tax behavior. Keywords: Tax Avoidance; Profitability; Institutional Ownership; Inventory Intensity; Agency Theory